2019
DOI: 10.1002/pbc.28138
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis‐associated malignant peripheral nerve sheath tumors in children have a worse prognosis: A nationwide cohort study

Abstract: Background Malignant peripheral nerve sheath tumors (MPNST) are rare and aggressive non‐rhabdomyoblastic soft‐tissue sarcomas (NRSTS) in children. This study set out to investigate clinical presentation, treatment modalities, and factors associated with survival in pediatric MPNST using Dutch nationwide databases. Methods Data were obtained from the Netherlands Cancer Registry (NCR) and the Dutch Pathology Database (PALGA) from 1989 to 2017. All primary MPNSTs were collected. Demographic differences were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 54 publications
(204 reference statements)
0
33
1
Order By: Relevance
“…However, the survival and recurrence of these patients were various in different literatures. Indeed, some factors were found as risk indicators in MPNST related literatures, such as NF 1 mutation [11,13,24,42], negative margin [13,24], non-adoption of adjuvant therapy [22,26], while several literatures [7,14,29,43] failed to nd prognostic power. Considering the disagreement on prognosis and risk factors, we performed the systematic review and meta-analysis to evaluate 5-year OS rate, 5-year EFS and LR rate of MPNST, and to investigate the related risk factors for survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the survival and recurrence of these patients were various in different literatures. Indeed, some factors were found as risk indicators in MPNST related literatures, such as NF 1 mutation [11,13,24,42], negative margin [13,24], non-adoption of adjuvant therapy [22,26], while several literatures [7,14,29,43] failed to nd prognostic power. Considering the disagreement on prognosis and risk factors, we performed the systematic review and meta-analysis to evaluate 5-year OS rate, 5-year EFS and LR rate of MPNST, and to investigate the related risk factors for survival.…”
Section: Discussionmentioning
confidence: 99%
“…For an Italian study focusing on pediatric patients (n=73) with relapsing MPNST, Bergamaschi, L. et al [28] reported that the survival rate was 15.8% at 5 years which was the lowest rate in our included studies. For non-NF 1 MPNST children (n=44) in the Netherlands, Martin, E. et al [42] showed the highest 5-year survival rate (75.8%) in these cohorts. In this study, the 5-year OS rate was 49% (range, 16%-63%), which consisted with the most published studies.…”
Section: -Year Os Rate 5-year Efs and Lr Ratementioning
confidence: 91%
See 1 more Smart Citation
“…However, the survival and recurrence of these patients were various in different literatures. Indeed, some factors were found as risk indicators in MPNST related literatures, such as NF1 status [11,13,30,48], negative margin [13,30], non-adoption of adjuvant therapy [28,32], while several literatures [7,14,35,49] failed to nd prognostic power. Considering the disagreement on prognosis and risk factors, we performed the systematic review and meta-analysis to evaluate 5-year OS rate, 5-year EFS and LR rate of MPNST, and to investigate the related risk factors for survival.…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of survival for the NF1 patients in past years, they considered that the survival difference was diminishing. However, NF 1 status has been reported to be a risk factor for the prognosis of MPNST in some literatures [11,30,48]. Porter, D. E. et al [42] founded that NF 1 was independent predictor of poor outcome due to the genetic pro le affecting aggressive potential, and emphasized the importance of NF 1 in MPNST staging.…”
Section: Risk Factors For Survivalmentioning
confidence: 99%